The Effect of Sectoral Output Volatility on Economic Growth in Ethiopia - Adisu Abebaw Degu (Journal of Economics, Business, and Accountancy Ventura, 2021)
This study examined the effect of sectoral output volatility on economic growth and the determinants of economic growth in the Ethiopian economy. The study used annual time series data spanning from 1981 to 2018 and included capital stock, working-age population, trade balance, and sectoral output volatility as an explanatory variable. Using the Exponential General Autoregressive Conditional Heteroscedasticity (EGARCH) and Autoregressive Distributed Lag (ARDL) cointegration test, the study found a long-run relationship between economic growth and economic growth explanatory variables. From the ARDL model, capital stock and trade balance (which has been negative throughout the study period) was found to have a positive and negative significant effect on the economic growth of Ethiopia, respectively. In the long-run, volatility of industrial and service sector output growth had a negative and statistically significant effect on the economic growth of Ethiopia. In recent years the role of agriculture in the Ethiopian economy, particularly in terms of contribution to the national GDP, has been declining—indicating the growing importance of service and industrial sectors. Therefore, smoothening and maintaining the positive sectoral output growth is advisable for the betterment of the economy. Besides, balancing the foreign trade and curbing unrestricted importation is recommended as long as economic growth is concerned.